Current Diagnosis and Treatment Approach to Sepsis - Aynur AKIN; Emine ALP; Mustafa ALTINDİŞ; Emel AZAK; Ayşe BATIREL; Yasemin ÇAĞ; Gül DURMUŞ; Esma KEPENEK KURT; Pınar SAĞIROĞLU; Zeynep TÜRE; Aslıhan CANDEVİR ULU; EKMUD Sepsis Working Group (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Sepsis is a major healthcare problem worldwide. Its mortality and morbidity is still high. Early diagnosis of sepsis and appropriate management in the initial hours improve outcomes. The Surviving Sepsis Campaign published new definitions for sepsis in 2016. In Sepsis-3 definitions, sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Organ dysfunction can be identified as an acute change in total SOFA score of at least two points consequent to the infection. However, this definition is endorsed by two international societies and there is much discussion regarding new definitions. Prospective validation of this definition on different levels is needed. The infectious source in sepsis depends on patients" underlying diseases and origin of the infection (community-acquired or healthcare-associated). In the literature, urinary tract and skin-soft tissue infection are the common sites in community-acquired sepsis, whereas respiratory system and intraabdominal infections are more common in nosocomial sepsis. Another challenge in sepsis management is the increasing incidence of sepsis due to multidrugresistant bacteria and limited treatment options. New antibiotics may be treatment options in the future. In this review, current definitions of sepsis, physiopathology of sepsis, foci of sepsis and causative microorganisms, microbiological diagnosis and rapid diagnosis methods, biomarkers used in the diagnosis of sepsis, antimicrobial treatment and resistance, new antibiotics and non-antibiotic therapy are discussed.